2014
DOI: 10.1093/pcp/pcu165
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cytochrome cM Stimulates Cyanobacterial Heterotrophic Growth in the Dark

Abstract: Although cyanobacteria are photoautotrophs, they have the capability for heterotrophic metabolism that enables them to survive in their natural habitat. However, cyanobacterial species that grow heterotrophically in the dark are rare. It remains largely unknown how cyanobacteria regulate heterotrophic activity. The cyanobacterium Leptolyngbya boryana grows heterotrophically with glucose in the dark. A dark-adapted variant dg5 isolated from the wild type (WT) exhibits enhanced heterotrophic growth in the dark. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…Leptolyngbya boryana (formerly Plectonema boryanum ) IAM‐M101 strain dg5 (Hiraide et al ., ) was used as the WT. NK4 is a mutant derived from dg5 , where the cnfR gene is disrupted by a kanamycin resistance cartridge (Tsujimoto et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Leptolyngbya boryana (formerly Plectonema boryanum ) IAM‐M101 strain dg5 (Hiraide et al ., ) was used as the WT. NK4 is a mutant derived from dg5 , where the cnfR gene is disrupted by a kanamycin resistance cartridge (Tsujimoto et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Recently, we reported that the cytM gene-encoding cytochrome c M has a function to suppress heterotrophic growth ability in the dark. A single adenine insertion in cytM was identified as the responsible mutation by comparison between genome sequences of the WT and a spontaneous variant dg5 showing faster heterotrophic growth [21]. This was confirmed by the phenotype of a cytM-disrupted mutant that was isolated through a targeted mutagenesis technique [21].…”
Section: Discussionmentioning
confidence: 90%
“…The cyanobacterial mutant YFB14 lacking chlB 26 was derived from Leptolyngbya boryana (formerly Plectonema boryanum ) strain dg5 36 , which was used as the host strain to overexpress chlB variants. YFB14 was cultivated in BG-11 medium with 15 µg ml −1 kanamycin under medium-intensity light conditions (40 µmol photon m −2 s −1 ) using fluorescent lamps as described previously 16 .…”
Section: Methodsmentioning
confidence: 99%